2001
DOI: 10.7326/0003-4819-134-7-200104030-00007
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Bone Marrow Lesions with Pain in Knee Osteoarthritis

Abstract: Bone marrow lesions on MRI are strongly associated with the presence of pain in knee osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

27
677
7
15

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 865 publications
(726 citation statements)
references
References 15 publications
27
677
7
15
Order By: Relevance
“…However, the lack of K-L Grade 4 patients in this retrospective case series is due to our general indication for this procedure as we deemed the most advanced grade of osteoarthritis to be a contraindication, as there is little reason to think that treating marrow edema below a bare joint surface would provide durable pain relief or regrow cartilage. In light of other studies [5,6] which have shown that the prevalence of symptomatic bone marrow edema lesions rises with increasing Kellgren-Lawrence Grade, we were not surprised by the negative correlation between K-L Grade and outcome scores. Our small sample size has been discussed as a limitation and we believe further studies with a larger number of study subjects would corroborate our finding.…”
supporting
confidence: 51%
“…However, the lack of K-L Grade 4 patients in this retrospective case series is due to our general indication for this procedure as we deemed the most advanced grade of osteoarthritis to be a contraindication, as there is little reason to think that treating marrow edema below a bare joint surface would provide durable pain relief or regrow cartilage. In light of other studies [5,6] which have shown that the prevalence of symptomatic bone marrow edema lesions rises with increasing Kellgren-Lawrence Grade, we were not surprised by the negative correlation between K-L Grade and outcome scores. Our small sample size has been discussed as a limitation and we believe further studies with a larger number of study subjects would corroborate our finding.…”
supporting
confidence: 51%
“…Enrollment age for women was older to lessen the chance of inadvertently subjecting a pregnant woman to radiography. The source of subjects for this study has been detailed in other publications (7)(8)(9). Briefly, subjects with knee pain were drawn from 2 cohorts receiving care at Veterans Administration Medical Centers and from the community.…”
Section: Methodsmentioning
confidence: 99%
“…Initial reports were extremely enthusiastic about the role of BMLs in knee OA. They suggested that BMLs were associated with knee pain [15], could be predictive of progression [16] especially if they enlarged [17] or were associated with varus or valgus angulation [16]. Later reports, however, were less clear-cut even suggesting that BMLs were not only unassociated with Western Ontario and McMaster Universities index of OA scores (WOMAC™) [18,19] and other measures of patient symptoms but also fluctuated over a period of time, resolving and/or worsening with new lesions coming and going elsewhere in the same joint [20,21].…”
Section: So Where Does the Problem Lie?mentioning
confidence: 99%